Becoming culturally intelligent: challenges and strategies among EFL students in IIUM - Idrus, Faizah; Mohamad Zamani, Nur Fadzilah; Omar, Bakri (2018)
Living in other parts of the world, especially being a student can be very challenging where it does not only require one to be physically strong but also mentally prepared to face all kinds of difficulties while being abroad. A predominant challenge would be language for academic and communication purposes. Despite having language and other challenges in the foreign countries, many of the international students in IIUM who are also EFL learners are also not aware of the concept cultural intelligence (CQ). Thus, the objective of this qualitative research is to examine how these EFL students perceive cultural diversity in Malaysia environment, as well as overcoming anxiety in speaking the English language in the EFL classrooms. Additionally, challenges faced by IIUM international students to be culturally intelligent and their learning strategies used to cope with those challenges will also be explored. An in-depth semi-structured interview guide is used to retrieve information from 6 postgraduate students from different kulliyah in IIUM in that thematic content analysis is employed to analyse the data. The findings suggest the importance of being culturally intelligent to overcome language anxiety and how the participants perceived cultural diversity in IIUM positively where they could enhance their people from different parts of the world. Another important finding is that lack of English proficiency among local students to communicate with the international students in a mutually intelligible manner, heighten the gap between them thus slowing down the acculturation process.